MODERN APPROACHES AND EDUCATIONAL SIGNIFICANCE OF MILITARY PEDAGOGY (Web of Teachers: Inderscience Research, 2025)
This article covers the essence of military pedagogy, its main tasks and modern approaches. It also reveals the use of pedagogical methods in the process of training military personnel, their role in the formation of patriotism, responsibility and disciplinary qualities in young men. The article also analyzes the problems and prospects of the military education system.